Construction of Distributed Databases and Application of Systems Theory and System Modeling in Education - Imnaishvili, Giorgi; Sirabidze, Nukri; Dumbadze, Zurab (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2025)
Systems theory was originally developed as a unifying approach to scientific research in different fields, which was intended to facilitate the emergence of more specific theories in individual disciplines. However, today, general systems theory is considered interesting not only as a general approach, but also as a specific theory for analyzing the functioning of individual systems in various fields.